Rosario+Vampire. 01, Vampires - Ikeda, Akihisa, 1976- (Shonen Jump advanced., 2008)
All-around average student Tsukune transfers to Monster High, where he discovers the turf war isn't between the jocks and the nerds but the vampires and the werewolves.